2016
DOI: 10.5194/acp-16-12733-2016
|View full text |Cite
|
Sign up to set email alerts
|

Deriving brown carbon from multiwavelength absorption measurements: method and application to AERONET and Aethalometer observations

Abstract: Abstract. The radiative impact of organic aerosols (OA) is a large source of uncertainty in estimating the global direct radiative effect (DRE) of aerosols. This radiative impact includes not only light scattering but also light absorption from a subclass of OA referred to as brown carbon (BrC). However, the absorption properties of BrC are poorly understood, leading to large uncertainties in modeling studies. To obtain observational constraints from measurements, a simple absorption Ångström exponent (AAE) me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
197
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 150 publications
(221 citation statements)
references
References 80 publications
(124 reference statements)
18
197
3
3
Order By: Relevance
“…5e). This observation implies that the BrC aerosol particles measured at the ATTO site are mixed down into the boundary layer in the early morning and are then quickly photo-degraded during the day (Forrister et al, 2015;Wang et al, 2016b;Wong et al, 2017). This pattern is not observed during the wet season, when σ ap BrC 370 exhibits no significant diel variability.…”
Section: Diel Cyclesmentioning
confidence: 80%
See 4 more Smart Citations
“…5e). This observation implies that the BrC aerosol particles measured at the ATTO site are mixed down into the boundary layer in the early morning and are then quickly photo-degraded during the day (Forrister et al, 2015;Wang et al, 2016b;Wong et al, 2017). This pattern is not observed during the wet season, when σ ap BrC 370 exhibits no significant diel variability.…”
Section: Diel Cyclesmentioning
confidence: 80%
“…10). We found that BrC contributes 24 % is ~1 day due to photolysis and oxidation, which destroy the chromophores (Forrister et al, 2015;Wang et al, 2016b;Wong et al, 2017). Therefore, BrC emitted from fires in the southern borders of the Amazon rain forest, which require ~3 days to be transported to the ATTO site, is likely to be significantly photodegraded and to contribute only weakly to total aerosol light absorption after atmospheric processing.…”
Section: Absorption Wavelength Dependence and Brc Contributionmentioning
confidence: 99%
See 3 more Smart Citations